Patient-derived tumor organoids for prediction of cancer treatment response. (December 2018) - Nagle, Peter W.; Plukker, John Th. M.; Muijs, Christina T.; van Luijk, Peter; Coppes, Robert P.
Abstract: Cancer treatment, in particular radiotherapy and chemotherapy, is often hindered by an inherent resistance of cancer cells. Cancer stem cells in particular have previously been shown to be more resistant than other cells within a tumor and are thought repopulate the tumour after therapies. Therefore, it is of utmost importance to develop tools and techniques that can be used to study mechanisms of resistance of cancer stem cells as potential treatment targets. Organoids (and cancer-derived organoids), are three-dimensional tissue-resembling cellular clusters derived from tissue or tumor specific stem cells that mimic the in vivo (tumor) characteristics, as well as (tumor) cell heterogeneity. Cancer organoids may further enhance the in vitro and in vivo models that are currently available, improve our understanding of cancer stem cell resistance and can be used to develop novel cancer treatments by improved targeting of cancer stem cells. In this review, we compare organoids with the more traditional laboratory models, such as cell lines and xenografts, and review the literature of the current role of cancer organoids in determining treatment responses.